Respective Contribution Research of Soft Component and Macroinitiator on Synthesis and Performance of MCPA‐PEA Materials. Issue 8 (3rd October 2017) - Xu, Sheng; Wang, Zhenxi; Liu, Lingli; Dai, Xin; Zhang, Shangxi; Cao, Meng
Abstract : The monomer casting polyamide‐polyether amine (MCPA‐PEA) materials initiated by TDI‐PEA macroinitiator presented an obvious toughness characteristic which was contributed by the combination effect of PEA‐TDI macroinitiator and soft PEA component itself. The MCPA‐PEA materials with different content of PEA‐TDI macroinitiator or PEA component were prepared and then the respective contribution of PEA‐TDI macroinitiator and soft PEA component on the synthesis and performance were researched. It was found that the PEA‐TDI macroinitiator presented the dominant contribution and main influence on the polymerization process with higher activation energy and reaction order than PEA component. The PEA molecular chains did not participated in the crystallization process and made no influence on crystal structure of MCPA material whatever the way of copolymerization or blending. The PEA‐TDI macroinitiator also showed the dominant contribution on the decreasing effect of crystallization properties than PEA component with lower crystallinity and smaller spherulites size. The fibrous‐structure for MCPA‐0.3%PEA matrix was more obvious with notable deformation and high impact strength which further indicated the dominant contribution of PEA‐TDI macroinitiator on toughness. The toughening mechanism was deduced as the vast energy consumption by intense extension of fibrous‐structure and the highly orientation of molecular chains. POLYM. ENG. SCI., 58:1353–1361, 2018. © 2017 Society of Plastics Engineers